Territorial Power and the History of a Lineage. The Intervention of the House of Moscoso in Santiago de Compostela from the 14th to the 16th Century - Galbán Malagón, Carlos J. (Madrygal. Revista de Estudios Gallegos, 2015)
During the Late Middle Ages, cities offered opportunities to those nobles who understood urban politics and its diverse aspects. This was made possible thanks to social and physical support. This stabilization of territorial nobility is perfectly exemplified by the constant confrontation between the Archbishop of Santiago and the city council. In order to analyse this, we will look into the role of a noble household –The Moscosos– regarding public life. We will include the family’s constant confrontation with the Church and their urban heritage, including those elements related to the Moscosos’ lineage within the city.